2017
DOI: 10.26510/2394-0859.pbe.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial evaluation of flowering stalks of Cistanche violacea, a holoparasitic plant collected from arid region in Qassim, Saudi Arabia

Abstract: Objective: Cistanche violacea has been found in Qassim region (Saudi Arabia), growing as a parasitic plant on Haloxylon salicornicum. The flowering stalk part of this plant was evaluated for antimicrobial potential against various referenced bacteria and fungi. Methods:The flowering stalk parts were collected from the field, dried, extracted by maceration in 80% methanol and 80% Ethanol, The crude extracts were examined against the tested microorganisms using agarwell diffusion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Finally, the recent study of Bouzayani et al (14) for samples collected from Sfax (southeast of Tunisia) showed important phenolic content and antioxidant activities for polar extracts, while evaluating the antimicrobial activity indicated that the methanol extracts had the highest activities. However, the methanol and ethanol extracts of C. violacea collected from the Qassim region of Saudi Arabia exhibited no or weak antimicrobial activity, except for Staphylococcus epidermidis, which had good activity (15).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the recent study of Bouzayani et al (14) for samples collected from Sfax (southeast of Tunisia) showed important phenolic content and antioxidant activities for polar extracts, while evaluating the antimicrobial activity indicated that the methanol extracts had the highest activities. However, the methanol and ethanol extracts of C. violacea collected from the Qassim region of Saudi Arabia exhibited no or weak antimicrobial activity, except for Staphylococcus epidermidis, which had good activity (15).…”
Section: Introductionmentioning
confidence: 99%